2011
DOI: 10.1016/j.vaccine.2011.04.031
|View full text |Cite
|
Sign up to set email alerts
|

The effects of vaccine characteristics on adult women's attitudes about vaccination: A conjoint analysis study

Abstract: The number of current and future vaccines for adults has been steadily increasing. Yet, vaccine coverage rates for adult vaccinations have historically been low, and less is known about how adults in the mid-adult age range make vaccine decisions for themselves. The purpose of this study was to assess which vaccine characteristics affect vaccine decision-making among mid-adult women. Adult women, aged 27–55 (n=258) rated 9 hypothetical vaccine scenarios, each of which was defined along 4 dimensions: mode of tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 30 publications
(34 reference statements)
0
11
0
Order By: Relevance
“…Given the National HPV Vaccination Program started almost ten years ago [49], somewhat surprisingly, our study participants were not strongly in favour of STI vaccines which may indicate lack of awareness of HPV being a STI. Parental studies reported similar results that a sexual mode of transmission had minimal impact on STI vaccine acceptability [27, 28]. Moreover, only 13% of adolescent girls were concerned about HPV in an HPV study conducted in the United States [7].…”
Section: Discussionmentioning
confidence: 98%
“…Given the National HPV Vaccination Program started almost ten years ago [49], somewhat surprisingly, our study participants were not strongly in favour of STI vaccines which may indicate lack of awareness of HPV being a STI. Parental studies reported similar results that a sexual mode of transmission had minimal impact on STI vaccine acceptability [27, 28]. Moreover, only 13% of adolescent girls were concerned about HPV in an HPV study conducted in the United States [7].…”
Section: Discussionmentioning
confidence: 98%
“…This method has now been applied to the study of patients' and physicians' health care preferences and decision making. [14][15][16] In this context, a medical decision or intended action is modeled as a function of potentially influential factors, or attributes, in the clinical situation and/or patient. These attributes are systematically varied across multiple case scenarios, which are then presented to study participants.…”
Section: Methodsmentioning
confidence: 99%
“…RBCA is a regression-based technique used to understand how product preferences are influenced by product attributes and has been validated for use in previous health-related research [18][19][20]. RBCA allows respondents to consider attributes simultaneously so that respondents can make trade-offs.…”
Section: Discussionmentioning
confidence: 99%